Exploring Ethnography of Outer Space: Methods and Perspectives (Anthropology of Now, 2025)
This book explores new methods and perspectives in the anthropology of outer space. For the past ten years, scholarship of outer space has grown significantly in the social sciences. Now, an international community of anthropologists is starting to produce significant contributions to this work. This is pushing the conversations around the future of humanity, technology, and outer space beyond the realm of speculative theory into concrete challenges to established norms within anthropology. Each chapter in this volume introduces a unique take on what constitutes an ethnographic field in anthropology. They signal a re-imagination of the central concept for the discipline and offer a timely meditation on the shift in anthropology’s understanding of fieldwork from its inception until now. The volume consists of eleven ethnographic chapters, plus an introduction by the editors, and two invited responses. Each of the main body chapters presents a distinct approach to situating outer space empirically on Earth. By bringing together emerging and established scholars, this book ultimately posits that an anthropological approach to outer space requires creative approaches to ethnography that are no longer exclusively premised on a co-presence with the people under study. A primer of innovative ethnographies and an ideal companion to courses on methods, this volume will provide students with a body of accessible, contemporary work on futurisms and outer space. In addition, this book will serve as a snapshot of a moment in ethnographically innovative anthropology that will be relevant to a wider academic audience through its exegesis of new methods for the study of distributed communities.